Antioxidant Activity of Methanol Extracts From The Stem Bark of Mangrove Plant Rhizophora mucronata - Mahmiah (University of Jember, 2017)
Numbers ofdiseases such as stroke, diabetes, gout, and even cancer are caused by the reaction of free radicals (oxidants) found in the body. Those diseases currently have notyet controlled. Deleteriouslifestyle, lack of exercise, or genetics can be the trigger to this oxidant. Based on Chemotaxonomic, drugs that have been used to inhibit the oxidation process or termination stage of free radicals contain the active ingredient in the form of secondary metabolitesof alkaloids, phenolics, terpenoids and steroids. For example, phenolic compounds such as flavonoids, xanthones, antioxidants and polyphenols is a good agent because it has a structure with a high degree of oxidation (Suares, et al, 2010).Researchesrelatedtothe exploration ofantioxidant active ingredient has been more focused on secondary metabolites found in terrestrialplants. The development of natural compounds potential of marine plant material such as mangrove are still not received much attention. Spalding et al. in 2001 explainedthat mangrovesplant in Indonesia is the highest in the world, both in terms of quantity area (± 42 550 km2) as well as the number of species (± 45 species). This basic natural resource of Indonesia mangroveiscertainly valuablepromising opportunities to be expandedas a biological drug.Mangroves plant that commonlyused as medicine discovered from various species i.e: Acanthus ilicifolius, Avicennia alba, Avicennia marina, Avicennia offinalis, Bruguiera cylindrical, Bruguiera exaristata, Bruguiera gymnorrhiza, Ceriops tagal, Hisbiscus tiliaceus, Ipomoea pes-capre, Lumnitzera racemosa, Nypa fructicans, Pluchea indica Rhizophora apiculata, Rhizophora mucronata and Sonneratia alba. Those plants are usually utilized as antiasma, antidiuretic, antidiabetic, reliever itching, and others. (Purnobasuki, 2004).The potential of mangroves as a drug is very important to be developed considering the need for drugs is increasingdealswith thegrowing of population and many kinds of diseases such as cancer, hypertension, tumor diseases and diseases caused by chemical or biological waste pollution fromviruses and bacteria. Peopleare more likely to choose drugs that are natural because relatively take few side effects or even none at all.Several studies of mangrove plants from genus Rhizophorathat have antioxidant bioactivity areshown in the crude butanol extract of mangrove R. apiculatawith IC5033.34 pg / mL (Gao, 2012). The methanol extract of R. mangle’sstem were also documented to haveantioxidant activity (Palacio, et al, 2014).One of mangrovesfound in Surabaya East Coastal (Pamurbaya), East Java, Indonesia is the mangrove Rhizophora mucronata. This mangrove species is indigenous mangrovesthat ethno-botanically popular used as a pain reliever and dyes natural wood. Secondary metabolites contained in the leaves, bark, stems, roots, and fruit aredifferent in quantity. The content of secondary metabolites in plant commonly used as a medicineisfromgeneral part of the bark. Therefore, on the basis of chemotaxonomic and ethno-botany of mangroves R. mucronata,this study aimsto explore the bioactivity of antioxidant from the stem bark of R. mucronata.